Oral administration of egg white ovotransferrin prevents osteoporosis in ovariectomized rats - Nan Shang; Xiaoyu Bao; Michael Doschak; Jianping Wu (Food Science and Human Wellness)
Ovotransferrin, an iron-binding glycoprotein, accounting for approximately 12% of egg white protein, is a member of transferrin fam ily. Our previous studies showed that ovotransferrin stimulates the proliferation and differentiation of osteoblasts, while inhibits osteoclastogenesis and resorption activity. The work aims to study the efficacy of orally administered ovotransferrin on the prevention of osteoporosis using ovariectomized (OVX) Sprague-Dawley rats. Oral administration of ovotransferrin showed no negative effect on body weight, food intake and organ weight. After 12-week treatment, feeding ovotransferrin at a dose of 1% (1 g ovotransferrin/100 g diet) prevented OVX-induced bone loss and maintained relatively high bone mineral density and integrated bone microarchitecture. The serum concentration of biomarkers indicating bone formation was increased in ovotransferrin administration groups, while the bone resorption biomarkers were decreased. Ovotransferrin feeding also decreased the production of serum cytokine TNF-α and IL-6, which are two stimulators for osteoclast differentiation. In addition to its direct regulatory role on bone turnover, ovotransferrin supplementation might benefit osteoporosis prevention by inhibiting adipogenesis, and regulating immune response. Our results suggested the potential application of ovotransferrin as a functional food ingredient on the prevention of osteoporosis.